u(8u-39)=5

Simple and best practice solution for u(8u-39)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for u(8u-39)=5 equation:



u(8u-39)=5
We move all terms to the left:
u(8u-39)-(5)=0
We multiply parentheses
8u^2-39u-5=0
a = 8; b = -39; c = -5;
Δ = b2-4ac
Δ = -392-4·8·(-5)
Δ = 1681
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1681}=41$
$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-39)-41}{2*8}=\frac{-2}{16} =-1/8 $
$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-39)+41}{2*8}=\frac{80}{16} =5 $

See similar equations:

| −6x−13=−x−23x= | | 2x+9=12-× | | 8x+9=9x-13 | | 5x-6-4x-13=0 | | 5x+6-4x-13=0 | | -4x+35=5(5+4x)+6x | | -8x+4+20x=-6x-14 | | 100=14t+t+10 | | q/2=20;10 | | 5x-12=2x-6(2x-3) | | |6x-1|=-13 | | 8x-65+5x+6=0 | | (2x+7)=99 | | 2x-(4x+2)=5x-30 | | 2/3x+4+1/5x=43 | | -8x+4(1+5x=-6x-14 | | 34+3x-21-7x=0 | | H=155-16t2 | | 11×y=616 | | x+5=2x+2(4x-2) | | -40+2x+34+3x=0 | | 3(7+7x)=189 | | -1+n/9=-2 | | 10=16-3x | | 2(n-4)-(7-3n)=4n | | 9(3c+5)=9 | | 3×3-2×3+u=(3×3×3-3×8)(2)+u | | 7+7n-4n=-11 | | 8u+26=2(u+7) | | 3/2x+6=0 | | 68+20x=350+20x | | 6x-25-40+2x=0 |

Equations solver categories